Implementasi Kurikulum Muatan Lokal Berbasis Pesantren Di SMP A. Wahid Hasyim Tebuireng Jombang - Nurkayati, Siti (Journal of Industrial Engineering & Management Research, 2021)
- This study aims to examine the implementation of the pesantren-based local content curriculum at SMP A. Wahid Hasyim Tebuireng Jombang. This study uses a qualitative-descriptive approach, with data collection techniques: observation, interviews, and documentation. The results of this study indicate: 1) Islamic boarding school-based local content curriculum in SMP A. Wahid Hasyim Tebuireng is more abundant than in junior high schools in general. Pesantren lessons are usually only available in madrasah schools, but at SMP A. Wahid Hasyim it is almost 40 percent of general lessons. 2) There are three supporting and inhibiting factors in the implementation of pesantren-based local content learning, namely the existence of a program to improve the quality of human resources (teacher training); adequate facilities and infrastructure; Teachers who support local content based on Islamic boarding schools have competent competencies and expertise in their fields. While the inhibiting factors are the lack of student interest in learning; input of students from public elementary schools; limited time allocation in Arabic subjects.